Effects of heterogeneous technological progress on haze pollution: Evidence from China - Yi, Ming; Wang, Yiqian; Sheng, Mingyue; Sharp, Basil; Zhang, Yao (Ecological economics, 2020)
Technological progress plays an important role in combating haze pollution in the long run. However, existing studies often ignore the inconsistent effects on the reduction of haze brought by different types of technological progress. Considering the potential heterogeneity among technological progress, this paper constructs a theoretical framework to analyse the impact of heterogeneous technological progress on haze pollution, using annual data from 30 provinces and cities in China for the period of 2003 to 2016. A systematic GMM method is applied to empirically test the effects of neutral technological progress and biased technological progress on haze pollution. The results show that first, due to cost-reduction effect and income effect, neutral technological progress and labour-saving technological progress are conducive to haze reduction; while the impact of capital-saving technological progress on haze pollution is insignificant. Second, because of the energy rebound effect, energy-saving technological progress cannot effectively reduce haze pollution. Third, the haze-reduction effects of different types of technological progress show significant regional heterogeneity in China. Last, in terms of the control variables, strengthening environmental regulation is the only factor that can be helpful in haze reduction, others intensify haze pollution.